Catalyst-Free Three-Component Synthesis of Spirobenzimidazolidines Bearing an Indole Scaffold - Moghaddam, F. Matloubi; Moafi, A.; Zamani, Z.; Daneshfar, M. (Synlett, 2018)
An efficient catalyst-free one-pot three-component reaction was developed for the synthesis of a new family of N- and S-containing spirocyclic compounds. Various derivatives of spirobenzimidazolidine containing an indole scaffold were synthesized for the first time in a modestly toxic solvent and under mild reaction conditions. The reaction times were of the order of several minutes, and all the products were obtained in moderate to high yields (overall yields 58–80%).
Keywords: indoles; benzimidazolidines; spiro compounds; multicomponent reaction; catalyst-free reaction